Фотоиндуцированные процессы переноса заряда в кристаллах CsI(Tl); Известия вузов. Физика; Т. 56, № 7, ч. 2 - Яковлев В. Ю. Виктор Юрьевич; Трефилова Л. Н. Лариса Николаевна; Карнаухова А. А. Анна Алексеевна; Косинов Н. Н. Николай Николаевич (2013, 2013)
Заглавие с экрана